2016
DOI: 10.4103/1119-3077.179285
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for Staphylococcus aureus and methicillin-resistant Staphylococcus aureus nasal carriage inpatients in a tertiary care hospital's chest clinic in Turkey

Abstract: The prevalence of nasal carriage of MSSA was low in our study population. The only risk factors playing role in carriage were found as being under the age of 65 and having prosthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In Turkey, two studies reported 1.2% prevalence of MRSA on hospital admission [26,27]. Another recent study from Turkey identified MRSA colonization in 6.2% of intensive care unit patients on admission [28].…”
Section: Discussionmentioning
confidence: 99%
“…In Turkey, two studies reported 1.2% prevalence of MRSA on hospital admission [26,27]. Another recent study from Turkey identified MRSA colonization in 6.2% of intensive care unit patients on admission [28].…”
Section: Discussionmentioning
confidence: 99%
“…There is a huge difference in the epidemiology of MRSA worldwide. For example, the prevalence of community-associated MRSA infection in Japan, Germany, Turkey, Taiwan, and Malta was found to be 0.94% [29], 1.2% [17], 1.2% [30], 3.8% [31], and 8.81% [6] respectively. These differences can be attributed to variations in microbiological methods (sampling technique, culture sites, and method of MRSA identification), local infection control standards, and the local prevalence of MRSA.…”
Section: Discussionmentioning
confidence: 99%
“…The profession, care unit and gender of the respondents were found to be associated with carriage rate of MRSA in this study but longer length of stay in service was not found to be associated. Socio-demographic characteristics such as age, gender, length of healthcare service and profession have been reported by previous studies to influence the carriage of S. aureus [25,26].…”
Section: Antibiotic Resistance Pattern Of Isolated Mrsamentioning
confidence: 83%